IMPLEMENTASI KEBIJAKAN PERALIHAN HAK MILIK ATAS TANAH UNTUK KEPENTINGAN UMUM PADA BAGIAN ADMINISTRASI PEMERINTAHAN UMUM SEKRETARIAT DAERAH KABUPATEN MAMUJU UTARA - Muharni, Muharni (Katalogis, 2016)
This study bertujuan untuk know switchover policy implementation property rights to land in the public interest on the part of the public administration Regional Secretariat of North Mamuju regency. This type of research is the study inikualitatif.Informan executor in the Secretariat of North Mamuju District and Land Office as well as policy targets. Collecting data using observations, interviews, and documentation, while the analysis of the data consists of data reduction, data presentation, and attractive transition policy menunjukkan implementasi research kesimpulan. Hasil property rights over land for public purposes in the general government administration Regional Secretariat of North Mamuju regency not maximized because resources and bureaucratic structures not running optimally due to the ability of human resources is still quite adequate and understanding of the field of the task is still lacking, and the implementation of the policy has not been according to SOP. But in terms of communication and disposition has been executed with the maximum, which means it has carried out the coordination and dissemination of clear and consistent as well as the executor attitude that shows awareness in doing a good job and the attitude demonstrated towards acceptance of the policy is executed.